Distinct benefit frames generate divergent effects of time scarcity mindset on prosocial behavior - Yang, Chen (Frontiers in Psychology, 2025)
Previous research has explored how time scarcity mindset influences prosocial behavior; however, the results have been inconsistent. The current research aimed to introduce benefit frames to examine the effect of time scarcity mindset on prosocial behavior. Inspired by the proposal that time scarcity mindset strengthens agentic (i.e., self-oriented) goals while weakening communal (i.e., other-oriented) goals, we assumed that benefit frames would moderate the impact of time scarcity mindset on prosocial behavior. We conducted a survey study (N = 282 participants) and an experimental study (N = 299 participants) to test this assumption. Our results indicated that under an others-benefit frame (i.e., benefits only to others), time scarcity mindset inhibited prosocial behavior, whereas this effect was attenuated under a self-and-other benefit frame (benefits to both oneself and others). These findings not only deepen our understanding of the effects of time scarcity mindset but also offer practical insights into how to mitigate its detrimental effect on prosocial behavior.